Gambaran Kesiapsiagaan Siswa SD di Desa Pusong dalam Menghadapi Bencana Tsunami - Hafiza Qaristy; Wheny Utariningsih; Maulana Ikhsan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Pusong Village, located in Lhokseumawe, is one of the areas in Aceh Province that has the potential to be hit by a tsunami based on geological conditions. The tsunami disaster can cause deaths and injuries and have an impact on public health problems, therefore disaster preparedness is needed especially for elementary school students who are a vulnerable group when a disaster occurs. The purpose of this study is to explain the preparedness of elementary school students in dealing with the tsunami disaster. The research method used is descriptive research with a cross sectional approach. The sampling technique used stratified random sampling, with 158 students as respondents. The results showed that the preparedness of elementary school students in Pusong Village in dealing with the tsunami disaster was in the low category with a frequency of 127 people (80.4%) with an average index value of 48.3 which included four sub-variables namely knowledge about disasters in the low category with frequency of 114 people (72.7%) with an average index value of 52.3, emergency response plans are in the low category with a frequency of 142 people (89.9%) with an average index value of 44.5, disaster early warning is in the low category. in the low category with a frequency of 154 people (97.5%) with an average index value of 24.7, and resource mobilization is in the low category with a frequency of 143 people (90.5%) with an average index value of 8.7 . The conclusion of this study is that elementary school students in Pusong Village have low disaster knowledge, emergency response plans, disaster early warning, resource mobilization and preparedness.